Development of UTAUT Model with Hedonic Motivation to Measure the Adoption of E-Marketplace Mobile Application in Indonesia - Prakarsa, Graha; Nursyanti, Reni (Sainteks: Jurnal Sain dan Teknik, 2025)
The development of internet users in Indonesia makes people enthusiastic about using internet services in conducting online shopping transactions using mobile e-marketplaces. This research is motivated by the main problem, namely the absence of measurements in previous studies that measure acceptance of the use of mobile e-marketplaces using the UTAUT model so that application developers can find out what factors can influence users in adopting existing mobile e-marketplaces. market system. in Indonesia. The data processed are 100 respondents who have experience using e-marketplaces on a mobile basis, then analyzed using PLS (Partial Least Squares). This study uses the conceptual framework of the Unified Theory of Acceptance and Use Technology (UTAUT) model. The constructs used in this study are Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Condition, in addition to the Hedonic Motivation variable. The results of the analysis show that Effort Expectancy and Hedonic Motivation have a significant effect on the actual use of E-Marketplace Mobile users in Indonesia, while Performance Expectancy, Social Influence and Facilitating Conditions have no significant effect on the actual use of E-Marketplace Mobile users in Indonesia. Keywords: : UTAUT, Hedonic Motivation, E-marketplace